Assessing oral health knowledge among public school children in Saudi Arabian subpopulation - Sultan Abdulrahman Almalki; Abdul Habeeb Adil; Mohammed Mustafa; Mohmed Isaqali Karobari (BMC, 2024)
Abstract Introduction Oral hygiene is paramount for maintaining optimal oral and physical health, especially among children who are particularly susceptible to dental caries and issues due to dietary habits and inadequate hygiene practices. This study aimed to evaluate the awareness and knowledge of oral health among public school children, analyse their oral hygiene habits, educate parents on the importance of oral health for their children, and implement an oral hygiene educational program in Al-Kharj City, Saudi Arabia. Methods Four public elementary schools were selected for the study, with a sample size of 200 school-going children participating. A structured questionnaire was used to assess awareness and knowledge of oral health among the participants. SPSS software version 26 was used for data analysis. Multiple regression analysis and correlation tests was employed to explore the relationships between the different variables measured in the study. Results The findings revealed a significant lack of awareness regarding oral health among school children. Oral hygiene habits were found to be inadequate in many participants. Overall, the findings highlight the need for targeted interventions aimed at promoting regular dental visits, addressing dental fear, and fostering positive oral hygiene practices among school-going children to improve oral health outcomes in the studied population. Conclusion The study highlighted a critical gap in oral health awareness among school children, underscoring the need for targeted interventions. While the oral hygiene educational program has been implemented and future data will shed light on its effectiveness, preliminary observations suggest that such programs could potentially improve oral health outcomes and overall engagement among students.